ECG interpretation made incredibly easy!. (Philadelphia, Pennsylvania : Lippincott Williams & Wilkins, 2005)
This book makes reading and understanding rhythm strips and 12-lead ECGs easy. This entertaining reference reviews fundamental cardiac anatomy and physiology, explains how to obtain and interpret a rhythm strip, and teaches the reader how to recognize and treat 18 arrhythmias. It also explains how to obtain and interpret 12-lead ECGs, posterior ECGs, and 15- and 18-lead ECGs. The familiar Incredibly Easy! elements found throughout the reference make it easy to remember key points
Cardiac anatomy and physiology -- Obtaining a rhythm strip -- Interpreting a rhythm strip -- Sinus node arrhythmias -- Atrial arrhythmias -- Junctional arrhythmias -- Ventricular arrhythmias -- Atrioventricular blocks -- Non-pharmacologic treatment -- Drugs that treat arrhythmias -- Obtaining a 12-lead ECG
Includes index.
Keywords: ELECTROCARDIOGRAPHY